Metal Resistance and Bactericidal Activities of a New Strain of Klebsiella Variicola Isolated from Iron Mine - R, Ray; Rani, Rina (Asian Journal of Biological and Life Sciences, 2016)
A bacterial strain was isolated from the top soil of an iron mine and was identified as Klebsiella variicola. The bacterial strain was found to achieve its maximal growth at 34°C and at a pH of 8.5 and attained stationary phase of growth at 43 hours. It showed resistance against a number of antibiotics that directly affect bacterial translation. The working strain was found to tolerate a variety of metal salts including Cr6+Cr3+,As2+,As3+, Al3+,Ag2+, Zn2+,Mn2+,Sn2+,Fe2+.Fe3+,Co2+, Cu2+,Cd2+,Pb2+ and Ni2+ at a high concentration. The multi-metal tolerance of the strain might have been attributed by the sticky slime produced by it, and the highest biofilm production was found in presence of lead salt followed by aluminum in the growth medium. The active compound secreted by the bacterial strain (bacteriocin) was found to check the growth of several Gram positive and Gram negative bacteria. The newly isolated strain of Klebsiella variicola could be effectively used in bioremediation of metal contamination and extension of shelf life of food materials.
Keywords: Bacteriocin; Bioremediation; Klebsiella sp; Metal resistance